OPTIMASI DIMENSI BALOK BETON BERTULANG PADA RUMAH BERTINGKAT SEDERHANA BERDASARKAN SNI -2847-2002 (SUBPROGRAM II PROGRAM PERENCANAAN TULANGAN BETON) - Septiropa, Zamzami (Jurnal Gamma, 2009)
o simplify the planning process needs reinforcement in reinforced concrete structures in simplehouses, which meet the requirements of security and comfort, requires the calculation process byusing a formula that is long enough that perhaps could only be understood by an engineer in thefield of Civil Engineering. In this subprogram II will be built a Dimension Beam OptimizationProgram Child and Parent Beams in Neutron Numerical approach Moment Style, Style and StyleNormal latitude necessary to determine the need for reinforcement beams. By simply entering someform of data input length of the beam on the program this application will get installed on thereinforcement requirements for reinforced concrete structures along with their material needs onthe job for the House Story Concrete Simple. Thus it is possible people will be able to calculateawampun needs reinforcement and concrete materials that are required on the job simple storyhouse.